"Communitas in Crisis": An Autoethnography of Psychosis Under Lockdown. (October 2021) - Fixsen, Alison
In this article, I use autoethnography to examine time spent on an acute psychiatric ward during the COVID-19 lockdown. I employ the device of "communitas in crisis" to emphasize the precarious nature of this experience and the extent to which, for myself at least, informal social interactions with fellow patients and "communitas" were significant features of my hospital experience and subsequent discharge. I suggest that a lack of emphasis on inpatient to inpatient relationships in the recovery literature is an omission and a reflection of psychiatry's authority struggles with both service users and professionals, along with a general perception of psychosis as individual rather than as a socially constructed phenomenon. I also suggest that, especially in the wake of greater social distancing, mental health and social services should safeguard against psychological and social isolation by creating more spaces for struggling people to interact without fear or prejudice.